Expanding the Mutation Spectrum Affecting αIIbβ3 Integrin in Glanzmann Thrombasthenia: Screening of the ITGA2B and ITGB3 Genes in a Large International Cohort. Issue 5 (May 2015) - Nurden, Alan T.; Pillois, Xavier; Fiore, Mathieu; Alessi, Marie‐Christine; Bonduel, Mariana; Dreyfus, Marie; Goudemand, Jenny; Gruel, Yves; Benabdallah‐Guerida, Schéhérazade; Latger‐Cannard, Véronique; Négrier, Claude; Nugent, Diane; et al.
Abstract : Glanzmann thrombasthenia (GT) is a rare inherited bleeding syndrome given by mutations in the ITGA2B and ITGB3 genes that encode the αIIbβ3 integrin that mediates platelet aggregation. Here, we have expanded the mutation spectrum in GT by screening ITGA2B and ITGB3 in 76 families and defining subtle changes in integrin structure leading to absent or aberrant integrin expression. Reference is also made to defects in genes involved in αIIbβ3 activation and variant GT‐like syndromes. ABSTRACT: We report the largest international study on Glanzmann thrombasthenia (GT), an inherited bleeding disorder where defects of the ITGA2B and ITGB3 genes cause quantitative or qualitative defects of the αIIbβ3 integrin, a key mediator of platelet aggregation. Sequencing of the coding regions and splice sites of both genes in members of 76 affected families identified 78 genetic variants (55 novel) suspected to cause GT. Four large deletions or duplications were found by quantitative real‐time PCR. Families with mutations in either gene were indistinguishable in terms of bleeding severity that varied even among siblings. Families were grouped into type I and the rarer type II or variant forms with residual αIIbβ3 expression. Variant forms helped identify genes encoding proteins mediating integrin activation. Splicing defects and stop codons were common for both ITGA2B and ITGB3 and essentially led to a reduced or absent αIIbβ3 expression; included was a heterozygous c.1440‐13_c.1440‐1del in intron 14 of ITGA2B causing exon skipping in seven unrelated families. Molecular modeling revealed how many missense mutations induced subtle changes in αIIb and β3 domain structure across both subunits, thereby interfering with integrin maturation and/or function. Our study extends knowledge of GT and the pathophysiology of an integrin.